Peran Mediasi Kepuasan Kerja pada Pengaruh Work From Home terhadap Kinerja di Masa Pandemi Covid-19 pada Karyawan Swasta di Kota Mataram - Apri Adi; Siti Nurmayanti; Hermanto Hermanto (Universitas Bumigora, 2022)
This study aims to determine the mediating role of job satisfaction on the effect of work from home on performance during the COVID-19 pandemic for private employees in Mataram City. The research approach used in this research is to use quantitative research methods. This study intends to explain the position of the variables studied and the influence between one variable and another so that the direct and indirect relationship between the variables of WFH, job satisfaction and performance is known. The population in this study is an unknown number of private employees in Mataram City who have done WFH during the covid-19 pandemic. The data collection method used is the survey method. The questionnaire consists of 39 statements distributed to 78 samples, namely private employees who meet predetermined criteria, namely private employees in the city of Mataram, employees who have done WFH during the Covid-19 pandemic and are 19-60 years old. The data analysis technique used path analysis. The results showed that: 1). The WFH variable has a positive and significant effect on performance. 2). The WFH variable has a positive and significant effect on job satisfaction. 3). Job satisfaction variable has a positive and significant effect on performance, and 4). Job satisfaction variable does not mediate the effect of WFH on.